MEMASAK DENGAN BAHAN DASAR MI SAGU - Iwan Setiawan; Kenji Septiandy (Politeknik Negeri Sriwijaya, 2023)
PKM based on kitchen introduction by focusing on how to process noodles into sago. This is done in order to increase the community's wisdom to increase by focusing on UMKM, so what happens to the community is how to focus on always improving the quality of life for prosperity. The situation that might occur is a shortage of supplies, and a situation that supports it by looking at how the process is going on by focusing on developing community empowerment efforts by increasing economic welfare. The activities carried out are aimed at focusing on high school students which can also be carried out in the midst of the surrounding community at DIAN BANGSA High School. PKM is carried out by having an output target, namely having knowledge-based basic capital which knows recipes and cooking ingredients as well as kitchen equipment. The process is carried out using sago noodles which have been processed with traditional ingredients and also without preservatives which have a fairly high health level. This activity was carried out with quite high enthusiasm where the participants really hoped for knowledge and to gain and be able to apply for this sago noodle business.